FACTORS AFFECT HAPPINESS IN WORK OF ACADEMIC SUPPORT STAFF IN RAJABHAT UNIVERSITY, RATTANAKOSIN GROUP - มีกิริยา โนรี; แสนเมือง อุทัยรัตน์ (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2018)
The purpose of this research were 1) to study the level of happiness of academic support staffs working 2) to compare the personal factors affecting to happiness of academic support staffs working and 3) to study the organizational factors that affect to happiness of academic support staffs working in the Rajabhat university of Rattanakosin Group. The methodology of this research was mixed between quantitative and qualitative. The samples were administrators and academic support staffs of Rajabhat university Rattanakosin Group. The research found that the happiness of academic support staffs working is in high level The internal factors affecting happiness in work at the highest level ascending order by companion environment, acceptance, commander, compensation, management process, work atmosphere, job content and the progress in work respectively. Therefore, the factors within the organization were positively correlated with work satisfaction at the high level.